Datasheet: Association of the rs1042522 SNP with prostate cancer risk: a study of cancer tissues, primary tumor cultures, and serum samples from a Spanish Caucasian population.xlsx - Toscano Guerra, Emily Marisol (2024)
assessment strategies. The TP53 gene, a tumor suppressor gene frequently mutated in cancer, commonly harbors the rs1042522 single nucleotide polymorphism (SNP), known as the P72R SNP, which may influence PCa susceptibility. This study investigated the prevalence of the P72R SNP in European Caucasian PCa samples and its association with PCa risk.MethodsGenotyping was conducted on 12 hormone-naïve aggressive PCa cultures (hnPCs) from untreated patients (Gleason ≥8), 11 radical prostatectomies (RP), and 94 serum samples using DNA Sanger sequencing and melting curve analysis. Comparative analysis utilized data from the GnomAD database’s European Caucasian non-cancer population.ResultsOur results demonstrate a significantly higher frequency of the P72R SNP in PCa samples and serums compared to the general European non-cancer population. A robust and statistically significant association (p < 0.0001) between the SNP and prostate cancer risk was identified, with an odds ratio of 7.937 (95% CI 5.37-11.00). Notably, the G allele (R72) showed a pronounced prevalence in high Gleason score (≥8) patients, although statistical significance was not reached. These results highlight a potential association with undifferentiated and malignant PCa lesions.ConclusionThe compelling association between the P72R SNP and prostate cancer risk underscores the potential utility of this marker for the early identification of patients at risk of aggressive metastatic prostate cancer. This insight could empower further research to intervene at an early stage by offering enhanced opportunities for timely and targeted interventions.